Evaluation of Formation and Evolution of Microporosity in Anodic Copper Solidification Processes: Simulation and Experimental Validation - Cruchaga-Ssa., M (2013)
The current study analyzes the formation and evolution of microporosity during the solidification of anodic cooper. The aim of this study is to develop a thermofluid-formulation including microstructural evolution and to perform experiments to validate some measured variables with the respective numerical predictions. To this end, a set of experiments is carried out in copper testing primary and eutectic phase formation together with porosity evolution. To evaluate the formation of different microstructural phases and porosity, anodic copper (99.80 pct purity, approximately) is poured into different types of molds. The effect of heat extraction on the thermofluid-microstructural response is evaluated using graphite and steel molds to promote different cooling rates. The microporosity depends on the microstructural formation; hence the microstructure needs to be firstly described. The proposed microstructural model takes into account nucleation and grain growth laws based on thermal undercooling together with microstructural evolution. The primary phase evolution model is based on both solute diffusion at the grain scale and the dendrite tip growth kinetics, while the eutectic evolution is assumed proportional to the copper initial composition and eutectic undercooling. The microporosity model accounts for the partial pressures of gases and the solute distribution in the liquid and solid phases. The corresponding numerical formulation is solved in the framework of the finite element method. Finally, the computed temperature, solid, and liquid volumetric fractions, and pressure histories together with the final values for the radius, density, and pore volumetric fraction, are all compared and validated with the experimental measurements. © 2013 The Minerals, Metals & Materials Society and ASM International.